2022
DOI: 10.1001/jama.2022.1738
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Physiologic Point-of-Care Cardiopulmonary Resuscitation Training on Survival With Favorable Neurologic Outcome in Cardiac Arrest in Pediatric ICUs

Abstract: IMPORTANCE Approximately 40% of children who experience an in-hospital cardiac arrest survive to hospital discharge. Achieving threshold intra-arrest diastolic blood pressure (BP) targets during cardiopulmonary resuscitation (CPR) and systolic BP targets after the return of circulation may be associated with improved outcomes. OBJECTIVE To evaluate the effectiveness of a bundled intervention comprising physiologically focused CPR training at the point of care and structured clinical event debriefings. DESIGN, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
40
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 44 publications
0
40
1
Order By: Relevance
“…The ICU-RESUS study was a multicenter, parallel, hybrid stepped-wedge cluster-randomized trial evaluating a two-part quality improvement bundle of physiology-directed point-of-care training and structured postresuscitation event debriefing compared with usual care ( 12 , 13 ). It was conducted in 18 pediatric and pediatric cardiac ICUs at 10 clinical sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The ICU-RESUS study was a multicenter, parallel, hybrid stepped-wedge cluster-randomized trial evaluating a two-part quality improvement bundle of physiology-directed point-of-care training and structured postresuscitation event debriefing compared with usual care ( 12 , 13 ). It was conducted in 18 pediatric and pediatric cardiac ICUs at 10 clinical sites in the United States.…”
Section: Methodsmentioning
confidence: 99%
“…These waveforms were reviewed and analyzed by blinded investigators (R.W.M., R.M.S.) at the Children’s Hospital of Philadelphia as previously described ( 13 , 16 , 17 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To the Editor We have some concerns about a recent trial that demonstrated that a bundled intervention of CPR training and postcardiac arrest debriefings did not improve patient survival to hospital discharge with favorable neurologic outcome among pediatric patients with cardiac arrest.…”
mentioning
confidence: 87%
“…The Improving Outcomes from Paediatric Cardiac Arrest—the ICU-Resuscitation Project, was a parallel, hybrid stepped-wedge, cluster randomised trial, involving 18 paediatric intensive care units (ICUs) from 10 North American hospitals [ 36 ]. The intervention comprised an ICU resuscitation quality improvement bundle consisting of (1) CPR training at the point of care on a manikin and (2) structured debriefings of cardiac arrest events focusing on physiological outcomes.…”
Section: Adrenalinementioning
confidence: 99%